Spatiotemporal variability of hydrogen and oxygen stable isotopes in the Han River Basin and the regional hydrological implication - Wu, Na; Yan, Ya-Ni; Zhang, Jun-Wen; He, Mei-Li; Zhang, Dong; Fu, Yu-Cong; Zhang, Gui-Shan; Zhao, Zhi-Qi (Frontiers in Earth Science, 2026)
Characterization of the spatiotemporal variability of stable isotopes (δ18O and δD) in the surface water of the Han River Basin (HRB) is critical for tracing basin-scale hydrological cycle processes, identifying moisture-source dynamics, and optimizing water resource management. Through systematic sampling and analysis of hydrogen and oxygen isotopes in the mainstream, tributary, groundwater, and rainwater of the HRB, we investigated the spatial and seasonal variation in the isotopic composition of water bodies in this area. The Local Meteoric Water Line (LMWL): δD = 7.72δ18O + 11.55 indicates that the study area is influenced by atmospheric precipitation and exhibits evaporative fractionation. The seasonal variation is closely related to the circulation effect and evaporative fractionation. The summer water isotope values (δ18O: −8.2‰, δD: −52.5‰) were significantly higher than those in spring (δ18O: −8.7‰, δD: −58.0‰) and autumn (δ18O: −8.6‰, δD: −56.6‰). This pattern can be attributed to two main factors: first, the moisture derived from the Western Pacific during summer exhibits inherently heavier isotopic composition (δ18O: −3.75‰, δD: −18.5‰); second, intensified evaporative fractionation further enriches heavy isotopes in surface waters. Across the Han River Basin, the spatial pattern of δ18O values follows an “increase-decrease-increase” trend from the Hanzhong Basin to the Qin-Ba Mountains, then to the middle and lower reaches. This trend is primarily controlled by the shifting dominance of three factors: groundwater discharge, tributary inputs, and direct precipitation. This study, for the first time, reveals that the seasonal variations of stable isotopes in surface water of the HRB are driven by circulation effect, providing a new isotopic tracing basis for hydrological analysis of watersheds in monsoon regions.